INTEGRATIVE APPROACH IN THE EDUCATION SYSTEM - M. E. Khurramov (Modern American Journals, 2025)
This article analyzes the concepts of "integration", "pedagogical integration", their meaning, the problems of integration in the educational process, the means and forms of implementing integration, the effectiveness of the integrated pedagogical system. The essence of the integrative approach is revealed, the approaches of scientists to the subject, the goals, principles, functions of the integrative approach are distinguished, the tasks of integrated courses are highlighted, the components of the integrative approach are identified
Keywords: Integration, pedagogical integration, integrative approach, principles, integrated courses, interdisciplinary connections, interdisciplinary lessons